OPTIMISASI KINERJA MESIN PENGOLAHAN TANDAN BUAH SEGAR MENGGUNAKAN METODE RCCP (STUDI KASUS PT. KARYA TANAH SUBUR) - Abdul Malik Ali; Arie Saputra; Junianto Putra (Jurnal Optimalisasi, 2017)
Successful planning and production controls require active capacity planning, in order to be able to meet the established master production schedules. Lack of capacity will lead to production failures, delays in delivery to customers, and loss of confidence in the formal system resulting in a decreased corporate reputation. Overcapacity will result in low resource utilities, increased costs, product prices become competitive, decreased profits. Standard time is a measure of completion of a production process for one unit of product with justified clearance. The standard time required to process 40 Ton bunches of palm fruit sterilizer is 94.70 minute/unit, for thresher machine 73,31 minutes/unit, for screw press machine 96,48 Minutes / unit, and oil purification machine 147,13 minute/unit. Efficiency is the ability of the machine to produce a product. The efficiency of sterilizer machine is 88.00%, for thresher machine is 88.00%, for screw press machine is 88.80%, and oil purification machine is 74.00%. Machine utility is the percentage of machine usage in units of time. The sterilizer machine utility is 81,33%, for thresher machine is 87,35%, for screw press machine is 86,88%, and oil purification machine is 83,18%. Capacity is the rate of output per unit time indicating that the facility theoretically has the ability to produce it. The sterilizer machine capacity is 81.33 ton/hour, for thresher bumper machine is 45,08 ton/hour, for screw press machine is 119,09 ton/hour, and oil purification machine is 79,49 ton/hour. The average production capacity of machine taken for two years is 27.61 ton/hour with machine capacity optimization level of 51,88 ton/hour.Keywords : Production Planning and Control, Standard Time, Capacity (RCCP).